A Noteon the Public Choice Approach to the Growth in Government Expenditure. (IMF Working Papers; Working Paper ;, 1988)
The paper applies an empirical model, based on the economic theory of public choice, to the Group of Seven countries. It is discovered: (a) that deficit financing does appear to contribute to increased real government spending; (b) that the demand for government services as a whole does not appear to be income elastic; (c) that there is some evidence of a productivity lag in the government sectors of Canada, Japan, and the United States, but not those of France, Italy, or the United Kingdom; and (d) that in most countries there is some evidence of economies of scale in the provision of government services.